Gaucher Disease and the Synucleinopathies. (28th May 2006) - Hruska, Kathleen S.; Goker-Alpan, Ozlem; Sidransky, Ellen
Abstract : Several recent observations suggest a connection between Gaucher disease, the inherited deficiency of glucocerebrosidase, and the synucleinopathies. Rare patients have been observed who develop both Gaucher disease and parkinsonism. Autopsy studies on these subjects reveal synuclein-positive Lewy bodies and inclusions. An increased incidence of synucleinopathies also has been noted in relatives of Gaucher probands. In complementary studies, screening of patients with parkinsonism has identified a greater than expected frequency of glucocerebrosidase mutations. These glucocerebrosidase mutation carriers have a wide spectrum of associated parkinsonian phenotypes, ranging from classic L-dopa-responsive Parkinson disease to a phenotype more characteristic of Lewy body dementia. Despite this association, the vast majority of Gaucher carriers and patients with Gaucher disease never develop parkinsonism. However, mutations in this gene are likely to be a contributing risk factor in subjects otherwise prone to developing synucleinopathies.